ВІРНІСТЬ ЯК РЕГУЛЯТОР ОСОБИСТІСНИХ ВЗАЄМИН СТУДЕНТІВ (Педагогіка вищої та середньої школи, 2009)
The article dials with the main approaches to understanding the term fidelity in personal relations of student's. The content structure of this term is presented.